Keberhasilan Implementasi Penggunaan Sistem Informasi Manajemen dan Akuntansi Barang Milik Negara dan Kinerja Individu - Ardyanti, Ni Wayan; Ariyanto, Dodik (E-Jurnal Akuntansi, 2020)
This study aims to determine the effect of the use of information systems and user satisfaction on employee performance. This research was conducted at the KPKNL Work Unit in Denpasar. The sampling method used in this study is nonprobability sampling based on saturated sampling technique. The analysis technique used is multiple linear regression analysis. The results of the analysis of this study stated that the quality of the system, the quality of information, the quality of collaboration and the quality of service had a positive and significant effect on system use and user satisfaction, and the use of the system and user satisfaction had a positive and significant effect on the performance of KPKNL work unit employees in denpasar area. Keywords: System Usage; User Satisfaction; Employee Performance; Simak BMN.